2022
DOI: 10.1002/jbt.23146
|View full text |Cite
|
Sign up to set email alerts
|

Zingiberene exerts chemopreventive activity against 7,12‐dimethylbenz(a)anthracene‐induced breast cancer in Sprague‐Dawley rats

Abstract: Breast cancer is the primary cause of cancer-related death in females, wherein increased mortality of breast cancer patients is recorded worldwide. Zingiberene is a monocyclic sesquiterpene from the ginger plant and has many pharmacological benefits. In this exploration, we assessed the anticancer actions of Zingiberene against the 7,12-dimethylbenz(a)anthracene (DMBA)-stimulated mammary carcinogenesis in rats and MDA-MB-231 cells. Breast cancer was induced in the Female Sprague-Dawley rats through the 25 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Our study aimed to determine whether ZBN, a powerful antioxidant, would have an otoprotective effect against PCX-induced ototoxicity. ZBN is a major component of Zingiber officinale and is a monocyclic sesquiterpene with essential medicinal properties including antioxidant [14], antibacterial [32], and antiviral [33], antiulcer [34], and anticancer [16,[35][36][37]. ZBN effectively decreased angiogenesis and inflammatory response, according to a recent study [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to determine whether ZBN, a powerful antioxidant, would have an otoprotective effect against PCX-induced ototoxicity. ZBN is a major component of Zingiber officinale and is a monocyclic sesquiterpene with essential medicinal properties including antioxidant [14], antibacterial [32], and antiviral [33], antiulcer [34], and anticancer [16,[35][36][37]. ZBN effectively decreased angiogenesis and inflammatory response, according to a recent study [38].…”
Section: Discussionmentioning
confidence: 99%
“…Next, a volume was calculated for each coronal slice using the software. Photoacoustic imaging with OxyHemo-Mode was utilized to assess the hypoxic volumes, and power Doppler was used for accessing the tumor vascularity. , …”
Section: Methodsmentioning
confidence: 99%
“…This observation indicated the importance of the compound’s natural form, hinting that other natural components in ginger or any natural product may play essential roles in their overall activity [ 140 ]. Several phenolic compounds such as 6-gingerol, 6-shagol, zingerone, and 6-paradol have shown oncolytic effects in various experimental models [ 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ]. Ginger extract inhibits breast tumor growth through the blockade of the G2/M phase.…”
Section: Plant-based Food Componentsmentioning
confidence: 99%
“…Another study showed a significant reduction in breast tumor growth in the orthotopic model of mice due to treatment with zerumbone, a cyclic sesquiterpene in ginger [ 152 ]. Seshadri et al found that zingiberene, a constituent of ginger, inhibited the 7,12-dimethylbenz(a)anthracene-induced breast cancer growth in Sprague–Dawley rats [ 151 ]. Zerumbone and 6-shogaol treatment arrested the growth of prostate cancer cells (DU-145) in the G1 phase.…”
Section: Plant-based Food Componentsmentioning
confidence: 99%